Vanished ebook Private justice series, book 1. - Hannon, Irene (Private Justice, 2013)
Tenacious reporter Moira Harrison turns to a handsome private detective to help her solve a mysterious disappearance the police say never happened—but someone will stop at nothing to keep the truth hidden.